The EEA Agreement in a Revised EU Framework for Welfare Services - Fløistad, Karin (Studies in European Economic Law and Regulation,, 2018)
This book addresses some of the most debated topics preceding the UK referendum on membership of the EU, namely welfare services and free movement of citizens. The work improves understanding of the implications of the European Economic Area (EEA) Agreement, which is the most integrated form of association agreement with the EU for non-member states. The author considers the impact of EEA law on both European Free Trade Association (EFTA) states and on EU Member States, and looks at case law. A broad range of welfare services are analysed, including public healthcare and educational services, various social services, and public utilities such as transport and public broadcasting. Free movement of students, of patients and public financing of welfare services are among the issues explored. The focus here is particularly on legal aspects and the demonstrated development of the EEA Agreement into the welfare sphere. This work enables a sophisticated analysis about the nature of the principles of homogeneity and dynamism. The book is essential reading for scholars who seek to understand the EU's legal framework, the EEA Agreement and its implications. The topics covered are also relevant to UK/EU discussions on future relations, both for intermediate and long-term arrangements.